Molecular characterisation of rice tungro bacilliform virus isolated from Bario, Sarawak - Sia, Magdline Henry Sum; Siew, Fung Yee (Malaysian Society for Microbiology, 2018)
Rice tungro disease is one of the most damaging and destructive diseases of rice in South and Southeast Asia. The disease is caused by the co-infection of two viruses, the Rice tungro bacilliform virus (RTBV) and Rice tungro spherical virus (RTSV). The symptoms and severity of the disease depend on these two viral agents, if rice is coinfected by both viruses, it will show the typical severe symptoms of yellow-orange leaf discoloration, plant stunting and reduced in yield. On the other hand, if rice is infected only with RTBV, it shows milder symptoms and in contrast, rice plants will show no symptoms if they are infected only with RTSV. The disease had been detected in Malaysia since the 1930s. However, the first incursion of the disease was only reported in Sarawak in 2012. Since the disease was not seen in the Sarawak until recently, very little information on local virus isolate is available. This study was conducted to obtain and record the nucleotide sequence of partial coat protein gene of two primary isolates of RTBV collected from Bario, Sarawak in 2012 and 2013. Methodology and results: Based on the phylogenetic analysis, the isolates cluster with the Southeast Asia group with sequence identity at nucleotide and amino acid level of 91.1 to 95.1% and 98.6 to 99.5% respectively. Conclusion, significance and impact of study: This study provide the first genetic information on RTBV isolates from Sarawak. This data is important for future reference of the virus variants and diversity for epidemiological and diagnosis purposes.